Water Bodies as a Catalyst to Growth and Development- The Case of Kodungallur Town, Kerala. (2016) - Bindu, C.A.; Mohamed, Abdul Razak
Abstract: The evolution and growth of cities and towns are primarily dependent on three important factors- Its geographic location, physical environment and its socio-economic environment. The presence of water in various forms in its natural setting plays an important role in enhancing the quality of physical environment and the socio-economic environment. During the processes of growth and expansion of cities and towns, the location of water bodies are seen by the planners and policy makers as liability and constrain rather than an asset or a resource. The development projects very often ignore the conservation of water bodies and transform them into other developments. Hence, the preservation, conservation and rejuvenation of water bodies in urban areas are important. The major factor that contributes to the sustainable development of an area is its water bodies. Moreover, presence of water bodies give added social, psychological and environment value. It includes (a) enhancing the aesthetic quality and place quality, thereby contributing to the image of the city or town (b)enhancing the social and recreational value and thus increasing the livability of the residents and land value many fold. In this paper the authors have made an attempt to (a) bring the importance of water bodies in an urban area to sustain its eco system (b) bringthe different ways by which the water bodies have acted as a catalyst to the growth and development of the town and (c) highlight the issues and potentials of the existing water bodies and (d) formulate strategies for sustainable development of town. These aspects are covered, in relation to a case study area Kodungallur town in Kerala State. In brief, the Kodungallur town is a culturally rich historical temple town of central Kerala. The town has its unique geographical advantage, historical and cultural importance and immense potential for growth and development.